Multi-scale habitat selection modeling identifies threats and conservation opportunities for the Sunda clouded leopard (Neofelis diardi). (November 2018) - Macdonald, David W.; Bothwell, Helen M.; Hearn, Andrew J.; Cheyne, Susan M.; Haidir, Iding; Hunter, Luke T.B.; Kaszta, Żaneta; Linkie, Matthew; Macdonald, Ewan A.; Ross, Joanna; Cushman, Samuel A.
Abstract: Clouded leopards are among Asia's most widely distributed felids, but also among its least known and most vulnerable. Clouded leopards occur in some of the most rapidly disappearing forests in the world, yet a comprehensive assessment of their status and habitat use is lacking, which in turn limits identification of their priority conservation needs and capacity to act as umbrella species for conserving associated forest biodiversity. To address this need for the Sunda species ( Neofelis diardi ), we applied multi-scale modeling to identify both key environmental variables influencing habitat use and optimal scales of relationship with these variables. We detected clouded leopards at 18.3% of 1544 camera stations and 17 of 22 sampling locations on the islands of Borneo and Sumatra. Multi-scale GLMM revealed that recent forest loss and large-scale plantations strongly and negatively influence clouded leopard detection. Our findings also suggest that higher elevations and ridges are important components of N. diardi habitat use. We illustrate how scale optimization of habitat use can provide critical information for characterizing the requirements of protected areas, and identify core habitat patches and connectivity gaps in need of future protection. Our findings indicate greater challenges facing clouded leopards on Sumatra, including higher poaching pressure, greater fragmentation, and roughly half the habitat area available to N. diardi on Borneo. This research contributes vital insights to assist in prioritizing habitat conservation networks for the protection of this vulnerable felid and the forest biodiversity for which it is an ambassador species.